ASSESSMENT OF MANAGERIAL COMPETENCE OF DEPARTMENT HEADS IN HIGHER EDUCATION INSTITUTIONS BASED ON R.S. NEMOV’S “LEADER” METHODOLOGY (International conference on multidisciplinary science, 2025)
This article explores the assessment of managerial competence in department heads of higher education institutions using R.S. Nemov’s “Leader” methodology. The study focuses on identifying key leadership qualities and management skills, including responsibility, influence, and strategic thinking. The results highlight the importance of socio-psychological factors in shaping effective academic leadership.